2011
DOI: 10.1177/1474651411406372
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diabetic foot according to Wagner’s classification in a rural teaching hospital

Abstract: Diabetic foot is a common, preventable complication of diabetes mellitus. This was a prospective study (April 2004 to October 2005) of 55 diabetic foot patients attending surgical out and in-patient departments at a rural hospital in Mahrastra, India. To determine the prevalence of diabetic foot amongst our patients with diabetes and the associated risk factors. All patients underwent medical assessment, including foot examination, those with diabetic foot answered an interviewer-administered questionnaire on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
1
10
0
1
Order By: Relevance
“…This reflects that most of our patients had late presentation with deep ulcer, osteomyelitis, and frank gangrene of the foot. Although individual surgeon practice may affect the decision to amputation, many studies have reported the association between higher Wagner grade with more extensive surgical intervention [9,35]. The mortality was also relatively high in this study (10.7%).…”
Section: Discussionmentioning
confidence: 45%
“…This reflects that most of our patients had late presentation with deep ulcer, osteomyelitis, and frank gangrene of the foot. Although individual surgeon practice may affect the decision to amputation, many studies have reported the association between higher Wagner grade with more extensive surgical intervention [9,35]. The mortality was also relatively high in this study (10.7%).…”
Section: Discussionmentioning
confidence: 45%
“… 36 The remaining five cohorts reported diabetes-related foot infections. 24 40 47 55 56 The prospective pooled prevalence estimate for diabetes-related foot infection was 3.4% (0.2–6.5); yet, statistical heterogeneity was again high and needs to be interpreted with caution. This is particularly the case considering the pooled prevalence estimate for diabetes-related foot infection was higher than for diabetes-related foot wounds.…”
Section: Discussionmentioning
confidence: 96%
“…This was most probably related to very few studies investigating a foot disease disorder or risk factor as their primary outcome of interest. 24 32 36 37 41 42 47 49 50 52 83 106 107 Most studies reported foot disease or risk factors as an additional aim to the primary study aim of investigating the prevalence of a larger condition, such as the total pressure ulcer or diabetes prevalence. This lack of focus on foot disease may have led to an under-reporting of prevalence findings as suggested in other similar studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations